PENGARUH RELATIONSHIP MARKETING TERHADAP LOYALITAS NASABAH PADA PT. BANK PEMBIAYAAN RAKYAT SYARIAH (BPRS) BERKAH DANA FADHLILLAH DI KABUPATEN KAMPAR PROVINSI RIAU - yusriadi yusriadi (Universitas Lancang Kuning, 2017)
Abstract: This research is meant to analyze and to test the influence of financial benefit, social benefits and structural benefits to the customer loyalty at PT. Bank Pembiayaan Rakyat Syariah (BPRS) Berkah Dana Fadhillah Regency Kampar. The sample collection technique has been done by using purposive sampling and the data analysis technique has been done by using multiple linear regressions and the samples are 140 people. The result of this research shows that financial benefits and structural benefits has positive and significant impact on customer loyalty. While social benefits have a negative and significant effect on customer loyalty. The suggestions in this study the company should be able to maintain and improve the implementation of relationship marketing on the dimensions of financial benefits and structural benefits and make improvements in terms of relationship marketing strategies on dimensions of social benefits.Keywords: Financial Benefit, Social Benefit, Structural Benefit dan Customer Loyalty